Ewosṭateans at the Council of Florence (1441): Diplomatic Implications between Ethiopia, Europe, Jerusalem and Cairo - Samantha Kelly (Afriques)
This article argues that at the Council of Florence, arguably the most important instance of European–Ethiopian diplomacy before the 16th century, the delegates representing the Ethiopian Orthodox Church were Ewosṭatean monks—schismatics, whose positions were not yet accepted by Ethiopian religious authorities nor permitted to other Ethiopian Christians. It further proposes that the monks’ participation in the Council of Florence was part of the Ewosṭateans’ larger strategy of pressuring Ethiopian authorities to adopt their own religious positions, at a time when the king’s sympathy for their views was not yet clear; that the Council of Florence highlighted Ethiopian tensions with the Coptic patriarch in a way that furthered the Ewosṭateans’ goals; and that subsequent events suggest that their participation in the Council did indeed contribute to their full incorporation in the Ethiopian Church, and possibly to King Zära Ya‘ǝqob’s interest in continued European diplomacy.